Antidiarrheal activity of methanolic leaf extract of Rumex vesicarius - Khan, Imran Ahmad; Janbaz, Khalid Hussain; Saqib, Fatima (Bangladesh Journal of Pharmacology, 2016)
This study evaluates the antidiarrheal activity of Rumex vesicarius (leaf) by using in vitro and in vivo assays. Antidiarrheal effect of R. vesicarius was evaluated using castor oil-induced diarrhea model in rat. Weight and volume of the intestinal content were assessed using the enteropooling method. Atropine (3 mg/kg, i.p) was used as positive control. R. Vesicarius at the doses of 200 and 400 mg/kg p.o. significantly retarded castor oil-induced enteropooling and intestinal transit. The gastrointestinal transit rate was studied and R. vesicarius at the doses of 200 and 400 mg/kg significantly inhibited (p<0.001) weight and volume of intestinal content. R. vesicarius caused concentration-dependent (0.011?mg/mL) relaxation of spontaneous contractions in isolated rabbit jejunum tissue preparation and inhibited K+-80 induced contractions (0.01-5?mg/mL), similar to verapamil, suggestive of calcium channel blockade. Results obtained herein indicate that R. vesicarius may contain effective compounds which can be used as an antidiarrheal agent.